Koherensi Surah dalam Tafsir Nusantara: Analisis Metode Penafsiran Buya Malik Ahmad dalam Tafsir Sinar - Juhri, Muhammad Alan (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
This article discusses the coherence of sura, a method of tafsir advocated by contemporary Western scholars, which has been recognized by Nusantara scholars. The focus here is on Buya Malik Ahmad, a Minangkabau scholar of tafsir who authored a work titled “Tafsir Sinar”. In addition to emphasizing the nuzuli (interpretation based on chronology of revelation) tafsir of sura, Buya Malik’s tafsir is also strongly infused with its coherence. By grouping verses into categories, Buya Malik seeks to demonstrate that the suras in the Qur’an form a cohesive and integral unity. This research identifies at least three characteristics of Buya Malik’s tafsir. First, Buya Malik not only establishes the internal coherence of sura but also its external coherence. Second, he categorizes verses not only based on the grammatical structure and thematic content of a sura but also based on information about its revelation (tartib nuzuli). Lastly, Buya Malik determines the main theme of a sura through its chronological order of revelation (tartib nuzuli). These three characteristics contribute a distinct perspective to the discourse on sura coherence, especially in the Nusantara region.